Falsely Elevated CA 15-3 Levels in Ovarian Sarcoidosis with Peritoneal Involvement and Ascites - Sotirios Tsiodras; Alina-Roxani Gouloumi; Zoi Tsakiraki; George Chrelias; Charalambos Chrelias; Stylianos Loukides; Ioannis Panayiotides (Hindawi Limited, 2018)
A rare case of ovarian sarcoidosis with peritoneal and omental involvement presenting as an ovarian malignancy is presented. Clinical, laboratory, and radiological evaluation of the patient revealed ascites and high levels of serum CA 125 and CA 15.3. The diagnosis of sarcoidosis was confirmed with pathology findings on tissues obtained during surgical laparotomy. Establishing the diagnosis of sarcoidosis can be treacherous and was complicated in this case by the falsely elevated biomarkers and ascites.